(untitled) (Journal of Pathology of Nepal, 2018)
Background: Many non-neoplastic and neoplastic lesions are encountered as cystic lesions of head and neck depending on the patient’s age and anatomical site. Value of FNAC in preoperative diagnosis of these lesions has been established in various study. Materials and Methods: The study was performed in 333 patients that presented as cystic lesions of head and neck at Department of Pathology, Tribhuvan University Teaching Hospital, Institute of Medicine, Kathmandu, Nepal from July 2013 to June 2014. RESULTS: Cystic lesions in head and neck accounted for 11.35% of all FNACs. The median age of the patients was 31 years and the majority of the patients were in the age group of 21-30 years with slight female predilection. Lateral neck was the most common site with lymph node (31.9%) the most common organ of involvement. Tuberculous lymphadenitis was the most common diagnosis with 21% of cases, followed by colloid goiter with cystic change and epidermal cyst. Pus was the most common aspiration finding. Sensitivity and specificity of FNAC in diagnosing malignancy was 83.3% and 100% respectively CONCLUSION: A significant number and wide variety of lesions present as cystic lesions of head and neck. FNAC is useful and cost effective tool to classify, diagnose and rule out malignancy in these cases.